Novel Palladium-Catalyzed Intramolecular Addition of Aryl Bromides to Aldehydes as Key to the Synthesis of 3,3-Dimethylchroman-4-ones and 3,3-Dimethylchroman-4-ols - Burke, Anthony (2019)
Many benzofused cyclic chiral alcohols are biologically active and a variety of synthetic methods has been developed to access these structures. Palladium‐catalyzed intramolecular nucleophilic addition reactions of aryl boron and aryl halide compounds to carbonyls are useful, but control over the cyclization to give a single product has to‐date proven challenging. Here, we describe the first controlled intramolecular nucleophilic addition of aryl bromides to aldehydes, providing the corresponding cycloalkanol or cyclic ketone derivatives simply by changing the base or the ligand. Ten new 3,3‐dimethylchroman‐4‐ol derivatives and six new 3,3‐dimethylchroman‐4‐ones were prepared (with up to 91% conversion and 46% ee).